2001
DOI: 10.1182/blood.v97.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 15: biology and relevance to human disease

Abstract: Since the cloning of interleukin (IL)-15 six years ago, there have been numerous studies examining the molecular and cellular biology of this cytokine. IL-15 and IL-2 have similar biologic properties in vitro, consistent with their shared receptor (R) signaling components (IL-2/15R␤␥ c ). However, specificity for IL-15 versus IL-2 is provided by unique private ␣-chain receptors that complete the IL-15R␣␤␥ and IL-2R␣␤␥ heterotrimeric high-affinity receptor complexes and thereby allow differential responsiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

22
810
3
10

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 858 publications
(859 citation statements)
references
References 281 publications
(305 reference statements)
22
810
3
10
Order By: Relevance
“…The concentrations of IL-15 produced by human islets were low, similar to data obtained in other cell types [49,52]. It has been shown that picomolar amounts of IL-15 are effective in maintaining NK cell survival in serum-free media [49], suggesting that the observed IL-15 production by human islets might be physiologically relevant.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The concentrations of IL-15 produced by human islets were low, similar to data obtained in other cell types [49,52]. It has been shown that picomolar amounts of IL-15 are effective in maintaining NK cell survival in serum-free media [49], suggesting that the observed IL-15 production by human islets might be physiologically relevant.…”
Section: Discussionsupporting
confidence: 79%
“…The main inducer of IL-15 in human islets and rat purified beta cells was IFN-γ. Similarly, IFN-γ induces IL-15 mRNA expression in monocytes and NK cells [49,50,51]. The concentrations of IL-15 produced by human islets were low, similar to data obtained in other cell types [49,52].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…IL-15 is a pro-inflammatory cytokine that was originally identified through its ability to induce T cell proliferation, displaying IL-2-like properties. 3 Indeed, both cytokines act through a heterotrimeric receptor that shares the IL-2 receptor (IL-2R , also referred to as IL-15R , CD122) and the common chain (IL-2R , CD132).…”
mentioning
confidence: 99%
“…3 Functionally, IL-15 plays a pivotal role in the differentiation and/or survival of natural killer (NK) cells, NK T cells as well as intraepithelial lymphocytes (IELs) and is critical for the maintenance of CD8 + memory T cells. 4 To identify factors that are involved in the formation of the HL-specific tumor microenvironment, we screened microarray gene expression profiles of HRS and B nonHodgkin cell lines with a special focus on cytokines and cytokine receptors.…”
mentioning
confidence: 99%